PENGARUH LINGKUNGAN KERJA,KEPUASAN KERJA,DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN (STUDI KASUS PADA UMKM AYAM GEPREK CIKARANG PUSAT) - Muhamaad Irsyad Halim; Moh. Rony Hidayah; Theresia Aprilia Br Sembiring; Aris Setiawan; Fakhri Hadi Satria (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This study aims to analyze the influence of the work environment, job satisfaction, and work discipline on employee productivity in UMKM Ayam Geprek Cikarang Pusat. Experimental methods with quasi-experimental designs were used in this study. Data was collected through questionnaires distributed to UMKM employees in Bekasi Regency. The population in this study was all employees with a total of 85 samples. This research used a saturated sample of 85 which was taken as part of the number and characteristics possessed. Research analysis techniques are carried out by testing using validity and reliability test methods, classical assumption tests and multiple linear regression tests. Validity and reliability testing shows that all variables are valid and reliable. Regression analysis shows that work environment and work discipline have a significant positive effect on employee productivity, while job satisfaction has no significant effect. Simultaneously, all three independent variables have a significant effect on employee productivity. The results of this study contribute to the understanding of the factors that affect employee productivity in UMKM. Companies are advised to improve the quality of the work environment and pay attention to aspects that can increase employee satisfaction and work discipline.